2010
DOI: 10.1002/bip.21522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the ΔPhe residue configuration on a didehydropeptides conformation: A combined CD and NMR study

Abstract: Conformations of two pairs of dehydropeptides with the opposite configuration of the ∆Phe residue, Boc-Gly-∆ Z Phe-Gly-Phe-OMe (Z-OMe), Boc-Gly-∆ E Phe-Gly-Phe-OMe (E-OMe), BocGly-∆ Z Phe-Gly-Phe-p-NA (Z-p-NA), and Boc-Gly-∆ E Phe-Gly-Phe-p-NA (E-p-NA) were compared on the basis of CD and NMR studies in MeOH, TFE, MeCN, chloroform, and DMSO. The CD results were used as the additional input data for the NMR-based determination of the detailed solution conformations of the peptides. It was found that E-OMe is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The strong positive bands at 220 nm and strong and broad negative bands at 270 nm are observed only for peptide Boc-Gly-Gly-D Z PhePhe-OMe in acetonitrile and methanol solutions. Such kind of spectra, as it was indicated before [58], is typical for tetrapeptide which is adopting type II b-turn, with DPhe at the i + 2 position. Also in case of tetrapeptide 2 the same tendency, which was show for tripeptide 1, to adopt less ordered conformation in less polar solvent is observed.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 94%
See 1 more Smart Citation
“…The strong positive bands at 220 nm and strong and broad negative bands at 270 nm are observed only for peptide Boc-Gly-Gly-D Z PhePhe-OMe in acetonitrile and methanol solutions. Such kind of spectra, as it was indicated before [58], is typical for tetrapeptide which is adopting type II b-turn, with DPhe at the i + 2 position. Also in case of tetrapeptide 2 the same tendency, which was show for tripeptide 1, to adopt less ordered conformation in less polar solvent is observed.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 94%
“…Secondary structure, adopted by hexapeptide 3 in DMSO, is stabilized by two intramolecular hydrogen bonds, which involved amide protons of Phe [3] and Gly [4] residues. Although temperature factor of the amide proton of Phe [3] is slightly bigger than 4.6 (ppb/K), we suggest that this proton participates in hydrogen bond formation, because chemical shift of this proton demonstrate significant independence from solvent polarity [58] (see Table 9). Obtained results for the tripeptide 1 and tetrapeptide 2 are similar to those obtained previously for their structural analogues containing E-isomer of DPhe [60].…”
Section: Nmr Spectroscopymentioning
confidence: 96%
“…Calculations of the lowest‐energy structures, carried out for the TASP molecules which exhibited ordered conformations in solution according to CD, were performed with an X‐PLOR NIH 2.21 program package . We used the same calculation procedure as in the conformational investigations of dehydropeptides . Each of 1000 structures was calculated using simulated annealing (initial temperature=1000 K, final temperature=100 K).…”
Section: Methodsmentioning
confidence: 99%
“…They contain a double bond between the C α and C β carbon atoms which results in their planar conformation and fixed values of the φ and ψ torsion angles. These features endow them with particular conformational properties . Recently, it has been found that peptides with α,β‐didehydro‐α‐amino acid residues can form hydrogels and may be used as a platform for drug delivery which make these residues important for medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%